EDUKASI KONSEP INTERNAL RATE OF RETURN PADA SISWA SMAN TAMANAN - Abdillah , Muhammad Sevi; Malatania, Lala Arum; Putri, Devina Amelia Eka; Rifta, Azzah Iftina; Roshiyana, Szasza Nazafah; Putri, Sonia Rahma Fajar; Damayanti, Asiska Fitria Bara; Safitriani, Alika; Gunasti, Amri (Universitas Mataram, 2024)
Technological advances make it possible to utilize natural resources efficiently. However, shortages occur when demand exceeds supply, making goods/services an economic object. This service aims to increase students' understanding of these concepts and provide provisions for them to face economic challenges in the future. Implementation of the activity began with a survey to determine the purpose of the school where this service activity was to be held. From the results of the survey we decided to carry out the service at SMAN Tamanan, followed by coordination with the teaching staff and submitting a permission letter from the campus for the service activity. A survey was conducted to determine student understanding, then a pre-test was carried out to assess initial understanding. Next, the material is delivered with discussion, followed by questions and answers to discuss concepts and review understanding. After that, a post-test was carried out to measure students' understanding after education, and continued with descriptive statistical analysis of the collected data. The results of this activity show a significant increase in students' understanding after receiving a comprehensive explanation. The pre-test and post-test showed an increase in student understanding, with 26% of students showing an increase in understanding after the socialization activities. This shows that this activity is effective in increasing students' understanding of the basic concepts of engineering and investment economics. Overall, this report shows that the use of technical economics at SMAN 1 Tamanan has succeeded in raising vocational teaching standards, preparing students to face the demands of the business world, and improving the local economy. These findings highlight the importance of incorporating engineering economics into vocational education curricula as well as the need to continue to foster the professional growth of students and administrators.